Workload in the Austrian IT-sector regarding leadership roles - Maria Gren (Frontiers in Sociology)
This paper investigates the impact of workload on leadership roles within the Austrian IT sector, by also paying attention to differences between genders. The research adopted a prospective design, selecting IT professionals, stratified by those with and without personnel responsibility and examined further through the lens of gender. A total of 200 participants completed the survey, where the modified German version of the Copenhagen Psychosocial Questionnaire (COPSOQ) served as the primary tool, which evaluated dimensions such as demands, influence, interpersonal relations, work interface, and conflicts. The results indicate that individuals with personnel responsibility experience significantly lower scores in the dimensions demands and influence, suggesting challenges in managing qualitative or emotional demands alongside perceived limitations in their scope of action. This trend persisted, albeit less marked, within the dimension work interface, indicating concerns regarding occupational stability (job security) among leading individuals. Gender analysis revealed that male participants reported fewer conflicts compared to females, highlighting discordance regarding experiencing workplace challenges. Discussion revolves around the difficulties faced by individuals with personnel responsibility in managing multifaceted demands of their role and the specific challenges encountered by female leaders. The findings emphasize the necessity of strategies to support leaders on acknowledging gender-specific challenges to enhance occupational health in the IT sector. This study contributes to the understanding of workload dynamics within leadership roles in the IT industry, recommending targeted measures to address the particular stress factors of leaders and highlight the need for gender-specific considerations in organizational support systems.